The islamic prohibition of adoption as limitation of the right to respect for family life (Article 8 ECHR) - revisiting ecthr harroudj v france, no 43631/09, 4 October 2012 - Koumoutzis, Nikos (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
The prohibition of adoption is common to many Muslim jurisdictions; it passes directly from religious law into statutory law. The French PIL incorporates this provision by making, in principle, foreign minors of prohibitive status ineligible for adoption. The question arises whether such restriction is compatible with the right to respect for family life (article 8 ECHR). In Harroudj v France, the ECtHR did not hesitate to respond in the affirmative. The paper revisits this judgment and concurs with what is deemed to be its ultimate finding, namely that a reduction on the level of satisfaction of the right to respect for family life may sometimes be justified as a token of tolerance or hospitality towards foreign ‘cultural law’.
Keywords: adoption; family life (article 8 ECHR); Islamic law; kafala; private international law